2012
DOI: 10.1017/s026114301100050x
|View full text |Cite
|
Sign up to set email alerts
|

The promotional state ‘after neo-liberalism’: ideologies of governance and New Zealand's pop renaissance

Abstract: AbstractThis article responds to Frith and Cloonan's (2008) call for researchers considering the relationship between the state and popular music to analyse more closely the ideologies of governance that undergird music policy. Building on Cloonan's ‘promotional state’ and drawing on recent New Zealand experience, this paper shows how New Zealand's Labour government (1999–2008) developed policies to support the export of ‘Kiwi’ pop which requires a reconsideration of state musi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In a situation analogous to what Cloonan (2007) has called ‘the promotional state’, the subsidy policy implemented by the government since 2007 has led to the government becoming Taiwan’s largest record company and investor. As Scott and Craig (2012) have pointed out, in the case of New Zealand, state coordination has led musicians to a more competitive market, which is an inevitable extension of the logic of neoliberal ideology. For example, many bands became only concerned about how to write a proposal in order to obtain a grant.…”
Section: Touming Magazine (透明雜誌) and Hom Shenhaomentioning
confidence: 99%
“…In a situation analogous to what Cloonan (2007) has called ‘the promotional state’, the subsidy policy implemented by the government since 2007 has led to the government becoming Taiwan’s largest record company and investor. As Scott and Craig (2012) have pointed out, in the case of New Zealand, state coordination has led musicians to a more competitive market, which is an inevitable extension of the logic of neoliberal ideology. For example, many bands became only concerned about how to write a proposal in order to obtain a grant.…”
Section: Touming Magazine (透明雜誌) and Hom Shenhaomentioning
confidence: 99%
“…54 Scott, in conjunction with David Craig (2012), then took the active involvement of the New Zealand government further by interrogating the 'promotional state'. Scott and Craig, in response to Simon Frith and Neil Cloonan's call to "analyse more closely the ideologies of governance that undergird music policy", 55 question the legacy of neo-liberalism and attempts by New Zealand's fifth Labour government to distance itself from the upheaval and turmoil of the neo-liberal 80s and 90s in New Zealand by becoming more interventionist in the cultural sector.…”
Section: Attempting To Contextualise New Zealand Music: Views From the Academymentioning
confidence: 99%
“…Keam (2006a) and(2006b), Lilburn (2011) and also examine New Zealand identity in relation to classical music (Keam and Lilburn) and the Cuba Street Carnival in Wellington (Brunt). 26 Shuker (2007Shuker ( ), (2008; Zuberi (2007); Scott (2008), ( 2012), (2013); Scott and David (2012); Stahl (2011) of the members of the local jazz community spent their formative years at the city's only jazz school, and it provides employment and performance opportunities for local professional musicians. Locating the NZSM's curricular and pedagogical approach within various critiques of jazz education, 27 I suggest ways in which the school's approach is reflected in the values and activity of the community.…”
Section: Discoursesmentioning
confidence: 99%
“…As outlined above, New Zealand popular music, although passionately pursued by its proponents, languished unsupported until the 1980s, when the left-wing Labour government "oversaw the state constitution of an 'institutional ecology' -an assemblage of subsidies, informal broadcast quotas, state-sponsored and co-ordinated social networks, formal and informal education programmes, and promotional activities that, in conjunction with shifting cultural norms around the value of domestic culture, founded the pop renaissance" (Scott 2013). Zuberi (2007), Scott (2008), ( 2012), ( 2013), Scott and Craig (2012), Shuker (2007Shuker ( ), (2008 and Shuker and Pickering (1994) Commission links the economic and cultural importance of music, asserting that "we can 71 Geoff Stahl (2011) surveyed a number of Wellington "indie" musicians, none of whom had received government funding, and found that in their experience the funding environment (consisting of central and local government bodies, policy and initiatives) was hegemonic and prescriptive, existing mainly to support mainstream acts and to perpetuate Wellington's (then) image as the "Creative Capital"; their comments echoed criticism of NZ On Air's funding strategy from other sources. 72 Often also "Kiwi music", a term criticised by Tony Mitchell (2010) as a "jingoistic" and "exclusionary" appeal to national pride.…”
Section: Popular Music Funding: Supporting 'Our' Musicmentioning
confidence: 99%